Sosialisasi e-modul gerakan pemanasan dan pendinginan dalam mata kuliah PJOK SD pada mahasiswa program studi PGSD - Andika, I Putu Herry Widhi; Angga, Prayogi Dwina; Putra, Gita Prima; Widiani, Silvia (CV. Global Cendekia Inti, 2024)
Students of the Elementary School Teacher Education Study Program at the University of Mataram still do not understand the material on elementary school PJOK warm-up and cool-down movements before and after the core activities. In addition, they have never received socialization about the e-module for elementary school PJOK warm-up and cool-down movements. Through the e-module for elementary school PJOK warm-up and cool-down movements, students not only learn the description of the material in the form of text and images but students are also facilitated in the form of learning videos. The purpose of this community service is to provide socialization of the e-module for elementary school PJOK warm-up and cool-down movements. The methods used consist of 4 stages, namely identifying partner problems, collecting data and planning solutions, and implementing solutions. The results of this activity are that the participants' knowledge and motivation to learn about elementary school PJOK warm-up and cool-down movements are increased.